(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the integration of blended learning models in the education of future teachers within higher pedagogical institutions. Given the rapid advancement of information and communication technologies, modernizing teaching approaches is essential to enhance professional competencies and independent learning skills among students. The study reviews key blended learning models, including Rotation, Flex, A La Carte, and Enriched Virtual, highlighting their practical applications and benefits in fostering student motivation, engagement, and academic success. Challenges in implementation, such as the effective use of Learning Management Systems and the incorporation of collaborative elements, are also discussed. The findings underscore the significant role of blended learning in preparing educators capable of utilizing digital technologies and innovative instructional methods to meet the demands of contemporary education and the labor market.